Environmental DNA and Hydroacoustic Surveys for Monitoring the Spread of the Invasive European Catfish (Silurus glanis Linnaeus, 1758) in the Guadalquivir River Basin, Spain - Ruth Coya; Amadora Rodríguez-Ruiz; Álvaro Fueyo; Carlos Orduna; Laura Miralles; Ilaria de Meo; Trinidad Pérez; Juan Ramón Cid; Carlos Fernández-Delgado; Lourdes Encina; Yaisel J. Borrell; Carlos Granado-Lorencio (Animals)
The European catfish (Silurus glanis Linnaeus, 1758) was introduced into the Ebro Basin in Spain in 1974 for recreational fishing. Since then, the species has spread throughout the country’s river basins, reaching the Iznájar Reservoir (Guadalquivir River Basin) in 2011. This area is of great ecological and economic relevance, especially as it includes the Doñana National Park, one of the most important nature reserves in Europe. Recently, the presence of catfish has been reported in the lower reaches of the river. In this work, we used non-invasive vertical and horizontal hydroacoustic surveys and environmental DNA river sampling to unravel the actual distribution and dispersal pattern of the species in the lower Guadalquivir River. The hydroacoustic profiles and the species-specific detections by real-time PCR (qPCR) and droplet digital PCR (ddPCR) showed that these non-invasive methods allow the detection and quantification of catfish and provide valuable information on the species’ presence. We have confirmed the presence of catfish in most of the study area, including downstream areas of the Guadalquivir Basin. The results suggest the possibility of other isolated introductions and/or human-mediated movements of specimens, and imply that a coordinated catfish prevention and mitigation strategy is therefore urgently needed.